Dam Breach Modeling and Downstream Flood Inundation Mapping Using HEC-RAS Model on the Proposed Gumara Dam, Ethiopia - Manamno Beza; Amdeselassie Fikre; Alene Moshe (Advances in Civil Engineering)
This study was, therefore, taken up to dam breach modeling and downstream flood inundation mapping. To achieve this objective, the software ArcGIS Version 10.4 extension program of HEC-GeoRAS Version 10 tool was used for HEC-RAS model development, to generate modeling reach and floodplain cross-sectional geometric data and for downstream inundation mapping and HEC-RAS Version 6.3.1 tool was used for subject dam break simulation and unsteady flood routing at downstream regions. Von Thun and Gillette regression equation was selected to estimate the breach parameter and the result shows that breach bottom width is 113 m, side slope 0.5H : 1V and breach development time is 0.85 hr for overtopping and bottom width is 111 m, and side slope 0.5H : 1V and breach development time is 0.83 hr for pipping. During analysis of flood routing the peak discharge at the dam site is 19,753.68 m3/s occurred at 4 hr for overtopping and 25,128.1 m3/s at time to peak 4 hr for pipping.